Analisis Faktor-Faktor yang Mempengaruhi Penggunaan Uang Elektronik : Studi Kasus Mahasiswa Fakultas Ekonomi dan Bisnis Islam Universitas Islam Negeri Sumatera Utara - Farhan Edma Manurung; Nur Ahmadi Bi Rahmani; Nurul Jannah (JIKEM: Jurnal Ilmu Komputer, Ekonomi dan Manajemen, 2023)
Electronic money is a means of payment in electronic form where the value of money is stored in certain electronic media, usually the transaction requires an internet network because its use uses a device such as a smartphone or computer. To obtain this electronic money, users must deposit or pay using physical money or cash to companies issuing electronic money to then store it in electronic media before using it for transaction purposes. Electronic money was first released in Indonesia in 2009 or about 10 years ago. This study aims to determine perceptions of trust, perceptions of security, perceptions of usefulness, and perceptions of ease of use of electronic money among students of the Faculty of Economics and Islamic Business, State Islamic University of North Sumatra. The type of data used is quantitative. The data used was obtained from distributing research questionnaires to students of the Islamic Faculty of Economics and Business, State Islamic University of North Sumatra, especially the class of 2019. The test tool used in this study was Spss.15 to test classical assumptions, multiple regression analysis, and hypothesis testing. The results of this study indicate that simultaneously perceived trust, perceived security, perceived usefulness and perceived convenience have a positive and significant effect on students of the Faculty of Economics and Islamic Business, State Islamic Universitas of North Sumatera Utara